2012
DOI: 10.1140/epjst/e2012-01605-4
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic resonant X-ray scattering: Beauty of forbidden reflections

Abstract: Abstract. Experimental results and their theoretical explanation are reviewed for fundamentals of anisotropic resonant X-ray scattering. Resonant scattering depends on X-ray polarization, i.e. the scattering reflects anisotropic environment of atoms in crystal. The polarization anisotropy in atomic scattering can excite the forbidden Bragg reflections. Studying this type of forbidden reflections we can distinguish electronic orbitals of specific symmetry. This method is very useful for studying local electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…Previously, ATS scattering has mainly been observed at transition metal K edges [41,42]. However, disentangling the physics from such K-edge measurements is difficult, as the K edge corresponds to 1s to np dipole transitions, where n is the first partially filled p shell, and higher-order transitions, (for example, the quadrupole transition is 1s to nd) can contribute.…”
Section: Energy Dependence Of Scattering From Un and U 2 N 3 Filmsmentioning
confidence: 99%
“…Previously, ATS scattering has mainly been observed at transition metal K edges [41,42]. However, disentangling the physics from such K-edge measurements is difficult, as the K edge corresponds to 1s to np dipole transitions, where n is the first partially filled p shell, and higher-order transitions, (for example, the quadrupole transition is 1s to nd) can contribute.…”
Section: Energy Dependence Of Scattering From Un and U 2 N 3 Filmsmentioning
confidence: 99%
“…A review about recent developments applying AAS and forbidden reflections can be found in Kokobun et al . . In 2012, further reviews appeared on the occasion of the Resonant Elastic X‐ray Scattering workshop 2011 concerning the development within the last 20 years in general and with specific focus on actinide systems , theoretical aspects as well as polarization analysis .…”
Section: History and Present Statusmentioning
confidence: 99%
“…For other examples and reviews on K -edge resonant diffraction experiments, see Refs. [12][13][14]. The study by Staub et al [11] was performed on NNO films grown using PLD on substrates of (001)-oriented NdGaO 3 substrates, which are also Pbnm.…”
Section: The Mit: Charge Disproportionationmentioning
confidence: 99%
“…14 RSMs around a (015) and b (005) for an LNO film compared to c (015) and d (005) for an LAO film, both with 100 nm thickness…”
mentioning
confidence: 99%